2018
DOI: 10.1186/s40814-018-0271-y
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of acute respiratory infections via improving the immune system in late preterm newborns with E. coli strain Nissle 1917: a controlled pilot trial

Abstract: BackgroundAcute respiratory infections (ARIs), caused by the high level of immaturity of the immune system, are a major cause of morbidity in preterm newborns. The probiotic Escherichia coli strain Nissle 1917 (EcN) is well known for its immuno-modulatory properties and may therefore enhance the immune competence. Thus, EcN administration may provide a promising possibility to decrease the risk of ARIs in this vulnerable group of children. However, clinical data supporting or refuting this hypothesis are, to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This was no longer observed at six or twelve months. There was a trend for fewer acute respiratory infections, of hospitalisations and shorter duration of these during the newborn period of up to 28 days, suggesting a more sustained beneficial effect of treatment [6]. E. coli Nissle 1917 may be effective against uropathogens [7] and antibiotic induced, rotavirus-associated gastroenteritis [8].…”
Section: Introductionmentioning
confidence: 99%
“…This was no longer observed at six or twelve months. There was a trend for fewer acute respiratory infections, of hospitalisations and shorter duration of these during the newborn period of up to 28 days, suggesting a more sustained beneficial effect of treatment [6]. E. coli Nissle 1917 may be effective against uropathogens [7] and antibiotic induced, rotavirus-associated gastroenteritis [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that EcN could trigger the production of anti-inflammatory mediators, such as IL-10, and suppress the immune response of lymphocyte T, macrophages, and other immunocompetent cells of both specific and nonspecific immunity, even at the systemic site [ 42 , 43 , 44 ]. In addition, EcN stimulated the systemic production of antibodies of B lymphocytes associated with the mucous membranes and induced the systemic production of antibodies (IgM, IgA) in adults [ 45 ]. The intestinal microenvironment and the engineered probiotic could, therefore, create a highly efficient and immunological-regulated antibody response on site [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As regards gastrointestinal diseases, probiotics were effective in reducing frequency and duration of diarrhea ( Francavilla et al, 2012 ; Park et al, 2017 ; Sharifi-Rad et al, 2020 ), reducing symptoms of gastroenteritis and H. pylori gastritis ( Shafaghi et al, 2016 ; Shin et al, 2020 ), and preventing necrotizing enterocolitis ( Chang et al, 2017 ). In respect of respiratory diseases, the benefit of probiotics has been mostly associated with prevention of infections, especially in the upper respiratory tract ( Aryayev et al, 2018 ; Anaya-Loyola et al, 2019 ; Lazou Ahrén et al, 2021 ). Finally, certain probiotics were successful in reducing symptoms and frequency of recurrent vulvovaginal candidiasis, bacterial vaginosis and urinary tract infections ( Laue et al, 2018 ; Russo et al, 2019 ; Sgibnev and Kremleva, 2020 ), possibly mainly by restoring the normal vaginal microbiota.…”
Section: Probioticsmentioning
confidence: 99%